The impact of promotional tools towards customer awareness at Mercedes-Benz Shah Alam / Nadirah Husna Mohamad Kamarudin - Mohamad Kamarudin, Nadirah Husna (Faculty of Business and Management, 2014)
This study is conducted to determine the impact of customer awareness towards promotional tools in Mercedes Benz Shah Alam. From this study, we can know either the customers of Mercedes-Benz Shah Alam aware about their product or service or not. If their customer aware about their product, we can see the promotional tools that Mercedes-Benz done are effective and efficiency. While, if Mercedes-Benz not reach the customer awareness in their company, it is show that their promotional tools are not effective and efficiency. On the other hand, from this study the researcher want to measure level of customer awareness at Mercedes Benz Shah Alam and want to identify the influences elements of promotional mix towards customer awareness at Mercedes Benz Shah Alam. Besides that, the researcher wants to determine the most influences factor towards customer awareness at Mercedes Benz Shah Alam and want to identify the alternatives to improve customer awareness at Mercedes Benz Shah Alam. Furthermore, this study was dedicated to the description of the methods and procedures done in order to obtain the data, how they will be analyzed, interpreted, and how the conclusion will be met. So that, from this study will obtain the level of customer awareness at Mercedes Benz Shah Alam which are high or low and the influences elements of promotional mix like advertising, personal selling, direct marketing, sales promotion and public relation towards customer awareness at Mercedes Benz Shah Alam. Besides that, the results from this study will gain the influences factor towards customer awareness at Mercedes Benz Shah Alam and the alternatives to improve customer awareness at Mercedes Benz Shah Alam.